Interpretasi Nilai Karakter Dalam Cerita Fabel Dayak Maanyan Kabupaten Barito Timur - Lazarus Linarto; Petrus Poerwadi; Indra Perdana; Nirena Ade Christy; Septi Apriliani; Siska Natalis Harapani (FKIP, Universitas Palangka Raya, 2024)
The Dayak Maanyan Fable is an important part of their oral literature, different from the fables in other regions in Indonesia. This fable story has unique characteristics because it involves local animals. This study aims to interpret character values ​​in five Dayak Maanyan Fable stories using descriptive qualitative methods and gadamer hermeneutics approaches. The stages involve interpretation, interpretive text, historical text, prejudice, data analysis, and prejudice. Through the Gadamer hermeneutics approach, Dayak Maanyan Fables from East Barito Regency revealed a number of significant character values. In the